2014
DOI: 10.1017/s0029665114001530
|View full text |Cite|
|
Sign up to set email alerts
|

Imaging methodologies and applications for nutrition research: what can functional MRI offer?

Abstract: Food intake is influenced by a complex regulatory system involving the integration of a wide variety of sensory inputs across multiple brain areas. Over the past decade, advances in neuroimaging using functional MRI (f MRI) have provided valuable insight into these pathways in the human brain. This review provides an outline of the methodology of f MRI, introducing the widely used blood oxygenation level-dependent contrast for f MRI and direct measures of cerebral blood flow using arterial spin labelling. A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 100 publications
(137 reference statements)
1
3
0
Order By: Relevance
“…In a previous fMRI study in fasted lean adults, De Silva et al demonstrated that the combined administration of PYY and GLP-1 attenuated brain areas that are involved in appetitive behavior, including amygdala, caudate, insula, nucleus accumbens, OFC, and putamen, thereby supporting that pharmacologic provision of these hormones ( 48 , 49 ), affects activation within brain areas included in our study. In another fMRI study following a test meal, ghrelin levels were associated with activation in the insula, amygdala, and OFC, while GLP-1 was associated with reduced activation in insula and OFC ( 50 ), demonstrating a potential relation between meal-induced changes of gut hormones and changes in brain areas involved in appetitive behavior.…”
Section: Discussionsupporting
confidence: 84%
“…In a previous fMRI study in fasted lean adults, De Silva et al demonstrated that the combined administration of PYY and GLP-1 attenuated brain areas that are involved in appetitive behavior, including amygdala, caudate, insula, nucleus accumbens, OFC, and putamen, thereby supporting that pharmacologic provision of these hormones ( 48 , 49 ), affects activation within brain areas included in our study. In another fMRI study following a test meal, ghrelin levels were associated with activation in the insula, amygdala, and OFC, while GLP-1 was associated with reduced activation in insula and OFC ( 50 ), demonstrating a potential relation between meal-induced changes of gut hormones and changes in brain areas involved in appetitive behavior.…”
Section: Discussionsupporting
confidence: 84%
“…These sensory experiences are associated with pleasant or occasionally unpleasant sensations (changes in mood and digestive well-being), i.e., the hedonic dimension of the sensory experience [12][13][14]18,19]. Changes in the activity of the central nervous system (CNS) in response to meal ingestion have been documented by means of functional brain imaging (e.g., functional magnetic resonance imaging and positron emission tomography) [20][21][22][23][24][25][26]. These studies reveal the crucial role of the CNS in the control of food intake and the conscious perception of sensation and in the maintenance of homeostasis [27].…”
Section: Food Ingestion and The Brain-gut Axismentioning
confidence: 99%
“…[43][44][45][46] In humans, changes in brain activity can be detected by different methods, such as functional magnetic resonance imaging and positron emission tomography. [47][48][49] The central nervous system plays a key role in homeostasis, control of food intake and perception of conscious sensations. 50…”
Section: Somatic and Homeostatic Responsesmentioning
confidence: 99%